CONTINUOUS MIDWIFERY CARE (CONTINUITY OF CARE) ON NY. W WITH MILK DAM AT THE FRISKAH NOVITA PRIMARY CLINIC MEDAN LABUHAN DISTRICT KABUPATEN DELI SERDANG YEAR 2025 - Agnes Asridevitiarni Nehe; Rosmani Sinaga; Friskah Novita; Adela; Dui Ronal Sihotang; Rieries Yuzil; Aprisilia Tarigan (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Breast milk dam is an increase in venous and lymphatic flow in the breast in order to prepare for lactation. This is not due to overdistension of the ducts of the lactation system of the dam due to overflowing of the lymphatic and venous dams before lactation. This study focuses on the relationship between the level of knowledge and the case of breastfeeding dams during the postpartum period. The main cause of the breast milk dam is the mother’s fluid milk output and the frequency of mothers breastfeeding their children is low so that there is a narrowing of the lactive duct, This case study describes the handling of the breast milk dam in Mrs. W at the age of 32 years. The care provided is to do breast massage and provide KIE about breastfeeding on demen ( once every 2 hours of breastfeeding) The purpose: of this service is to increase the mother’s understanding of the prevention and handling of breast milk dams in mothers at the Pratama Friska Novita clinic. Methods: The method used in this study is education and administration of Fe tablets. The results of this study show an increase in pregnant women’s knowledge about breast milk dams and how to handle them. In conclusion, provide counseling and perform breast massage actions in handling cases in this region.